Mapping finance sources for nature-based solutions in Africa - Laetitia Pettinotti; Adriana Quevedo (Overseas Development Institute (ODI), 2023)
Nature-based solutions for green infrastructure - such as managing fresh water flows, improving agricultural productivity or planting native vegetation - provide multiple benefits to people, communities and their environment. As it stands, countries seeking to identify finance for nature-based solutions must navigate complex fragmented terms and language, as well as a wide array of public and private finance actors. Such fragmentation has practical implications. African countries face multiple, simultaneous procedures to access funding for nature-based solutions, each with different demands on their capacity. Adding to the complexity, finance for nature-based solutions often combines public and private financing. So far, blended financing has been limited to international climate funds and multilateral development banks (MDBs), while private financing remains largely limited to philanthropic investment. This report lays out existing and potential sources of funding for nature-based solutions, covering current sources of public finance and exploring domestic and international public finance, blended finance stakeholders, and private funding sources.
Keywords: 330; Finance; Bio-diversity; Global risk; Climate; finance; Africa; Climate change; Green growth